Stedman's medical dictionary : illustrated in color - Stedman, Thomas Lathrop (Philadelphia : Lippincott Williams & Wilkins, 2006)
A dictionary that is a reliable resource for healthcare, including medical students, physicians, educators, researchers, and medical language specialists. It includes more than 107,000 terms and definitions.
Includes bibliographical references and index.
Keywords: Medicine; Medicine; Medicine